2005
DOI: 10.1037/0278-7393.31.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Right Hemisphere Sensitivity to Word- and Sentence-Level Context: Evidence From Event-Related Brain Potentials.

Abstract: Researchers using lateralized stimuli have suggested that the left hemisphere is sensitive to sentence-level context, whereas the right hemisphere (RH) primarily processes word-level meaning. The authors investigated this message-blind RH model by measuring associative priming with event-related brain potentials (ERPs). For word pairs in isolation, associated words elicited more positive ERPs than unassociated words with similar magnitudes and onset latencies in both visual fields. Embedded in sentences, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
143
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(173 citation statements)
references
References 63 publications
27
143
2
1
Order By: Relevance
“…Further evidence that the RH is capable of message-level processing was obtained in an ERP study (Coulson, Federmeier, Van Petten, & Kutas, 2005) that varied sentence congruity and lexical association independently, equating cloze probability across associated versus nonassociated conditions in sentence contexts similar to those used in Faust, Bar-lev, & Chiarello (2003). The responses for both VFs showed robust priming for lexical associates out of context.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…Further evidence that the RH is capable of message-level processing was obtained in an ERP study (Coulson, Federmeier, Van Petten, & Kutas, 2005) that varied sentence congruity and lexical association independently, equating cloze probability across associated versus nonassociated conditions in sentence contexts similar to those used in Faust, Bar-lev, & Chiarello (2003). The responses for both VFs showed robust priming for lexical associates out of context.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 97%
“…Prior ERP studies have shown that both hemispheres are broadly sensitive to basic manipulations of plausibility/expectancy (Federmeier & Kutas, 1999a;Coulson, Federmeier, Van Petten, & Kutas, 2005;Federmeier, Mai, & Kutas, 2005), manifested as larger N400 amplitudes to implausible or unexpected endings as compared with N400s to expected endings. However, such studies have also indicated that the two hemispheres use context information differently, as facilitation for unexpected endings related to a predicted completion is observed on N400 responses only with RVF/lh presentation (Federmeier & Kutas, 1999a), and as effects of expectancy on the amplitude of the P2, a component linked to higher-order visual processing, are also evident only for RVF/lh items (Federmeier & Kutas, 2002;Federmeier, Mai, & Kutas, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAT was chosen based on its established use in the literature (e.g. Coulson et al, 2005) and because rank of association is regarded as a more optimal measure of association than association frequency (Anaki and Henik, 2003). Mean association strength for association word-pairs are shown in Table 3.…”
Section: Stimulimentioning
confidence: 99%
“…If, instead, syntactic structures are closely bound to specific lexical entries and syntactic structures are accessed and activated via specific words, only the repeated condition should lead to a reduction in the amplitude of the P600 at the word by in the target sentences. N400 modulations as a function of semantic facilitation may occur at the repeated past participle (e.g., Besson & Kutas, 1993;Ledoux et al, 2007) but may not be present for the synonymous participles, because semantic priming effects are not always observed when the preceding sentence or discourse context is highly constraining (e.g., Camblin, Gordon, & Swaab, 2007;Coulson, Federmeier, Van Petten, & Kutas, 2005;Van Petten, Weckerly, McIsaac, & Kutas, 1997). Alternatively, if facilitative effects in processing target sentences are not related to priming of the syntactic structure per se but instead result from priming as a function of the semantic match between the prime and the target sentences because the past participles are repeated or synonymous, we would not predict a reduced P600 on by in either of the conditions.…”
Section: Methodsmentioning
confidence: 99%